Socio-economic inequalities in minimum dietary diversity among Ethiopian children aged 6–23 months: a decomposition analysis - Worku, Nigusu; Workie, Amare Mesfin; Yohannes, Lamrot; Getnet, Mihret; Negash, Wubshet Debebe; Yeshambel Belay, Adina; Asmare, Lakew; Alemu, Hiwot Tadesse; Geberu, Demiss Mulatu; Jejaw, Melak; Demissie, Kaleb Assegid; Tiruneh, Misganaw Guadie; et al. (Frontiers in Public Health, 2025)
BackgroundGlobally, inappropriate feeding practices account for more than two-thirds of all cases of child mortality during the first 2 years of a child’s life. For a long time, Ethiopia has suffered from the double burden of malnutrition: overnutrition and undernutrition both pose significant challenges, particularly for children. Undernutrition is mainly caused by wealth and educational disparities across the country. Therefore, this study aimed to assess the socio-economic inequalities in minimum dietary diversity (MDD) practices among Ethiopian children aged 6–23 months and the potential contributing factors.MethodsThe study utilized the recent datasets of the Ethiopia Mini Demographic and Health Survey (EMDHS) of 2019. A total of 1,511 weighted samples were included in the research. Microsoft Excel and STATA v.14 software were employed to extract, clean, and analyze data. A probit model decomposition analysis was performed. The concentration index (CIX) and curve were used to examine household wealth status and maternal education level inequalities in the MDD.ResultsThe total weighted prevalence of MDD among children under the age of 5 in Ethiopia was 13.5%. Wealth and educational status show positive CIX values for inequality, as exhibited by the concentration curve under the equality line. The CIX with household and maternal education status were (CIX: 0.1034, p < 0.0029) and (CIX: 0.1057, p < 0.0002), respectively. This indicates a greater concentration of inequalities among privileged women. The decomposition analysis revealed that household wealth status, (58.23%) contributed by wealth status, (36.38%) place of delivery, (30.47%) maternal education, and (21.5%) administration region, explained the pro-rich inequalities in MDD in Ethiopia.ConclusionThis study identified significant inequalities in terms of wealth and maternal educational level in the context of MDD. Policymakers and healthcare workers should develop effective strategies to tackle the underlying causes of inequalities in attaining MDD, specifically focusing on household wealth and maternal education.